Strategic Marketing and Competitive Advantage of Selected Petroleum Products Marketing Companies in Nigeria: The Moderating Role of Resource Capabilities - Alao, Abiodun E.; Adefulu, Adesoga D.; Asikhia, Olalekan U.; Makinde, Olubisi G. (Journal of Accounting, Business and Finance Research, 2020)
This study investigated the effect of strategic marketing on competitive advantage and how resource capabilities moderated the effect. A cross-sectional survey research design was adopted. Based on population of 1568 managerial staff of selected petroleum products marketing firms in Lagos State, Nigeria, Cochran’s formula was applied to determine a sample size of 564. Response rate of 497 respondents was achieved in the study. Data collected were analysed using multiple regression analysis. The findings established that strategic marketing has a positive and significant effect on competitive advantage (R = 0.594, Adj. R2 = 0.627, F (4, 491) = 208.685, p = 0.000 < 0.05) and that resource capability has no significant moderation on the effect of strategic marketing on competitive advantage (ΔR2= 0.000, ΔF (1, 493) = 0.0305, p > 0.05) of the selected petroleum marketing companies in Lagos State, Nigeria. The study recommended that the management of petroleum products marketing companies should be committed to adopting strategic marketing in order to improve competitive advantage.